2008
DOI: 10.1007/s00420-007-0296-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychosocial factors at work and life style on health and work ability among professional workers

Abstract: Objectives The purpose of this article is to explore the associations of psychosocial factors at work, life style, and stressful life events on health and work ability among white-collar workers. Methods A cross-sectional survey was conducted among workers in commercial services (n = 1141). The main outcome variables were work ability, measured by the work ability index (WAI), and mental and physical health, measured by the Short-Form Health Survey (SF-12). Individual characteristics, psychosocial factors at w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
98
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 15 publications
13
98
3
5
Order By: Relevance
“…This study enables a wider understanding of the role of health behaviors in long term work ability, because earlier studies have mostly included single health behaviors in cross-sectional settings [9][10][11][12][13][14][15][17][18]. As the trajectory analyses showed, unhealthy behaviors may cluster and affect, one another, which is why it is relevant to investigate the cumulative effects [47].…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This study enables a wider understanding of the role of health behaviors in long term work ability, because earlier studies have mostly included single health behaviors in cross-sectional settings [9][10][11][12][13][14][15][17][18]. As the trajectory analyses showed, unhealthy behaviors may cluster and affect, one another, which is why it is relevant to investigate the cumulative effects [47].…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…In addition, one cross-sectional study found a linear association with alcohol consumption among 31-year-old women and non-significant u-shaped association among men [17]. In another study, a negative association was only found among older workers [18]. No longitudinal studies exist.…”
Section: Introductionmentioning
confidence: 99%
“…Work-related predictors include environmental and ergonomic conditions and physical and mental demands 14 . Factors for life outside of work involve the support of family and friends, well-being and satisfaction with life 24,25 . It should be emphasized that even though these predictors are presented separately, they relate dynamically and form a network connected to the sustainability of WA; understanding how these interactions occur may be critical to WA preservation 1,26 .…”
Section: Predictive Factors For Wamentioning
confidence: 99%
“…As a result, changes in work ability have been investigated on a group level as changes in the mean scores of the work ability index. In this respect, previous research has shown that mean scores of the index are lower for older age groups of employees (5,(18)(19)(20)(21)(22) and for employees with physically demanding work (5,21). However, by analyzing the mean scores in predefined groups, information is gained only regarding the common trends, and, for example, there is a risk that any atypical development paths of work ability remain undetected.…”
mentioning
confidence: 99%
“…These factors included managers' background characteristics (age, managerial level), perceived work resources (supportive organizational climate, job control), and work attitudes (job involvement, organizational commitment). After an examination of the literature on work ability and occupational health, we hypothesized that younger age and higher managerial level would predict positive work ability trajectories (5, Feldt et al [18][19][20][21][22][31][32][33]. We further hypothesized that high levels of work resources would serve as favorable factors for the development of work ability (15,21,22,32,(34)(35)(36)(37)(38), as would high job involvement and organizational commitment (39).…”
mentioning
confidence: 99%